Intercultural empathy between Palestinian and Israeli individuals : a qualitative study utilizing grounded theory - Jackson, Kelsea Jayne (2017)
This study addresses intercultural empathy as a concept, and if or how it might be present among conflicting parties, specifically between Palestinian and Israeli individuals. Since there are many definitions of the word “empathy,” the researcher examines previous definitions of this term, how it relates to intercultural empathy, and then offers a singular definition for the purpose of this study. Previous research has examined empathy in relationship to other familiar words, including “sympathy” and “compassion,” though there has been little research done on the term, “intercultural empathy,” as a whole, nor has it often been studied between specific conflicting parties. Through interviews over Skype, as well as through open-ended survey questions, the researcher analyzes how Palestinian and Israeli individuals conceptualize “intercultural empathy” as a concept, and how said individuals perceive the “other” in relationship to the amount of contact they have had with the “other.” It is intercultural empathy that might enable us to better realize our shared humanity.